(untitled) (Journal of Rangpur Medical College, 2023)
Abernethy syndrome is defined as the congenital diversion of portal blood away from the liver either end-to-side shunt or, side-to-side shunt. Here we are reporting a case of a 15-year-old boy presented with recurrent encephalopathy and uncontrolled hypertension. Persistent rise in blood ammonia level was noted with normal other biochemical parameters. Ultrasound and Doppler study of the abdomen revealed drainage of the portal vein into the inferior vena cava and a small size of the left kidney. Renal artery angiogram and hepatic angiogram were performed, which confirmed the diagnosis of Type 1B Abernethy syndrome with left renal artery stenosis. After counseling the patient and his parents and taking consent, he has been treated with Left renal artery angioplasty, antihypertensive along supportive treatment. The treatment of Abernethy syndrome depends on its type, associated congenital anomalies, and complications. If possible closer of thes hunt is the mainstay of treatment but in case of type 1 malformation with the absence of the possibility to close the shunt may require a liver transplant. J Rang Med Col. September 2023; Vol. 8, No. 2: 56-59